Kajian Ilmu Rasm Usmani dalam Mushaf Al-Qur’an Standar Usmani Indonesia - Arifin, Zaenal (Lajnah Pentashihan Mushaf Al-Qur'an, 2013)
This writing will answer the skeptical attitude of some people about the authenticity of the Othmani MushafÃ‚Â Al-QurÃ¢â‚¬â„¢an with the Othmani standard of Indonesia from the aspect of narration and its scientificÃ‚Â epistemology. The method being used in this research is descriptive analysis. After being observed from some sources and being analyzed by some literature studies, either epistemologically or narrative, the Mushaf al QurÃ¢â‚¬â„¢an with Othmani standard is still referring to the basic of the pattern of the writing of the Mushaf al QurÃ¢â‚¬â„¢an with the Othmani writing and is still in accord with it. In the field of the science of writing the Mushaf (Rasm) is still in the corridor of the agreement which is embodied in the 6 principles of the basic principles of the science of writing of the Othmani, and all are still consistently followed and thus, the argument of theÃ‚Â al-Itqan by as-Suyuti (w. 911 H) which is considered to be Ã¢â‚¬Å“less authoritativeÃ¢â‚¬Â in the field of writing the Mushaf of the QurÃ¢â‚¬â„¢an can be defeated.